IMPLEMENTASI SANKSI PIDANA BAGI PELAKU TINDAK PIDANA ANAK DI PENGADILAN NEGERI MERAUKE - Erni Dwita Silambi (Universitas Musamus, Merauke, Papua, 2015)
So important is the problem of children so that all nations across the world, has a great attention to the child. The issue of child protection criminal is very important because after the child offender is the next generation and the future of a nation.with the criminal justice system, Indonesia has had its own laws, namely Law No. 11 Year 2012 on Child Justice , Where this law has been designed as a means of dealing with cases of children in court. That is inevitably a central point of children who commit criminal acts lies in judge reseach aims to determine.Implementation of State Merauke court criminal sanctions against children as a criminal and what factors were taken into consideration in imposing sanctions judge with criminal using empirical juridical , Which is expected to address issues. In implementation factors that are considered by the judge in order for sanctions that include the factor of juridical and non-juridical factors. While the juridical and practical probleme relating to the application of sanctions pertaining to juvenile criminal procedural law and procedural law in general. While the actions of judges in the future have the same goal in realizing the objective of sentencing with the perspective of child protection and child welfare.